2023
DOI: 10.1007/s11482-023-10229-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Short-Term Study in China Programs: Voices of Hong Kong University Students

Lu Yu,
Mingyue Gu,
Shengquan Ye
et al.

Abstract: Despite the mounting evidence supporting the effectiveness of short-term study abroad programs (such as Service-Learning programs) on university students’ development, few studies have been conducted to explore the impact of short-term study in China programs on young people from Hong Kong. This study employed a qualitative design method to examine the impact of three types of short-term study programs in China—summer school, cultural tour, and service-learning—on Hong Kong university students’ development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…However, Lou’s empirical study located in the postcolonial context observed that a close identification with China led to better cultural adaptation and greater acceptance of other groups when Macau students interact in Mainland China (2021). This finding is consistent with a study of Hong Kong students studying in Mainland China, which showed that a local Hong Kong identity (vs. a Chinese national identity) was associated with worse adaptation experiences ( Yu et al, 2023 ). Based on the existing literature, the current study hypothesized that Macau students with a strong national identity (i.e., Chinese), instead of a local identity (i.e., Macanese), will have better psychological states.…”
Section: Literature Reviewsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Lou’s empirical study located in the postcolonial context observed that a close identification with China led to better cultural adaptation and greater acceptance of other groups when Macau students interact in Mainland China (2021). This finding is consistent with a study of Hong Kong students studying in Mainland China, which showed that a local Hong Kong identity (vs. a Chinese national identity) was associated with worse adaptation experiences ( Yu et al, 2023 ). Based on the existing literature, the current study hypothesized that Macau students with a strong national identity (i.e., Chinese), instead of a local identity (i.e., Macanese), will have better psychological states.…”
Section: Literature Reviewsupporting
confidence: 91%
“…In one exception, Dai and Liu (2021) used convenience methods that included 63 mainland college students studying in Hong Kong and Macau to investigate their adaptation levels. In another line of study that explores the adaptation of students of former colonial enclaves studying in Mainland China, a dominant literature also employed qualitative methods (e.g., Lee et al, 2020 ; Yu et al, 2023 ). In one exception, Lou (2021) adopted a quantitative approach to examine the importance of language and social identity of Macau students transitioning to universities in Mainland China.…”
Section: Methodsmentioning
confidence: 99%